High frequency of BRAF mutations in primary mucinous ovarian carcinoma of Taiwanese patients - Wan-Ru Chao; Yi-Ju Lee; Ming-Yung Lee; Gwo-Tarng Sheu; Chih-Ping Han (Elsevier, 2021)
Objective: Considering the clinical evidence of BRAF inhibitors that can treat melanoma patients successfully, we aimed to investigate the status of BRAF mutations of primary mucinous ovarian carcinomas (MOC) in Taiwanese women, and apply the emerging paradigm classification of BRAF mutation groups. Materials and methods: 20 archived primary MOC samples were analyzed. The BRAF mutations of activation segment (exon 15), CR3 (conserved regions 3), kinase domain of the BRAF gene were analyzed using the highly sensitive BRAF mutant enriched kit (FemtoPath®) with Sanger sequencing method. Additionally, we extended our prior reported data of HER2 aberrations and KRAS mutation into this study in order to compare with the status of BRAF mutation. Results: Of them (n = 20), 16 (80%) harbored BRAF missense mutations. Their mutation profile and case number (n) were categorized as (1) class I: V600E (n=1), V600M (n = 1); (2) class II: A598V (n = 1), T599I (n = 10); (3) class III: none (n = 0); and (4) unclassified variants: S602F (n = 2), T599I/S602F (n = 1). The BRAF S602F is novel. The prevalence of BRAF mutation is significantly higher than either HER2 mutation (80% vs. 35%; p = 0.022) or HER2 amplification (80% vs. 35%; p = 0.022). However, the mutation rates of BRAF and KRAS were not significantly different (80% vs. 60%; p = 0.289). Conclusion: Activating BRAF mutation, HER2 amplification, HER2 mutation and KRAS mutation were not mutually exclusive. However, they may even have a synergistic effect in tumorigenesis. BRAF mutation is not uncommon in primary MOC of Taiwanese. The BRAF mutant (T599I) stands the majority. We suggested that there was a lower potential response to the existing V600 BRAF inhibitors, but may be responsive to dual BRAF plus MEK inhibitors or single MEK inhibitor. Further studies are warranted to investigate the clinical benefits of newly targeted therapy in recurrent or advanced stage primary MOC patients carrying different classes of BRAF mutation.